Indandione‐Terminated Quinoids: Facile Synthesis by Alkoxide‐Mediated Rearrangement Reaction and Semiconducting Properties. (22nd November 2019) - Du, Tian; Gao, Ruiheng; Deng, Yunfeng; Wang, Cheng; Zhou, Qian; Geng, Yanhou
Abstract: A series of 1, 3‐indandione‐terminated π‐conjugated quinoids were synthesized by alkoxide‐mediated rearrangement reaction of the respective alkene precursors, followed by air oxidation. This new protocol allows access to quinoidal compounds with variable termini and cores. The resulting quinoids all show LUMO levels below −4.0 eV and molar extinction coefficients above 10 5 L mol −1 cm −1 . The optoelectronic properties of these compounds can be regulated by tuning the central cores as well as the aryl termini ascribed to the delocalized frontier molecular orbitals over the entire molecular skeleton involving aryl termini. n‐Channel organic thin‐film transistors with electron mobility of up to 0.38 cm 2 V −1 s −1 were fabricated, showing the potential of this new class of quinoids as organic semiconductors. Abstract : Elektronik‐Bausteine : 1, 3‐Indandion‐terminierte Chinoide mit variablen Endgruppen und Kernmotiven wurden durch eine Alkoxid‐vermittelte Umlagerungsreaktion synthetisiert. Die Eigenschaften dieser Chinoide können über die Art der Kernmotive und der Aryl‐Endgruppen reguliert werden. Die Verbindungen zeigen unipolare Halbleitereigenschaften vom n‐Typ mit Elektronenmobilitäten von bis zu 0.38 cm 2 V −1 s −1 .